Assessment of senescence on oral mucosal model treated with bisphosphonate / Nur Bashira Shaharuddin - Nur Bashira, Shaharuddin (2017)
Osteonecrosis of the jaw (ONJ) has been associated with bisphosphonate (BP) treatment of Paget’s disease of bone, bone metastases, as well as postmenopausal and steroid-induced osteoporosis. The inhibition of bone resorption has been effectively employed in bone-disease treatment, but bisphosphonate-specific toxicity on oral mucosa causes impaired soft tissue healing followed by the onset of inflammation. The modern generation of BPs that contain a nitrogen group (N-BPs) have been intravenously administered to improve the management and prevention of complications associated with bone cancer metastasis, but they are potent and accumulate in the bone. This study presents results of the construction of a three-dimensional model comprised of an airliquid interface co-culture of normal immortalized oral keratinocytes (OKF 6/TERT 2) and normal human oral fibroblasts (NHOF). Co-culture of OKF 6/TERT 2 and NHOF in a tissue construct resulted in stratified epithelium and expression of differentiationrelated protein such that the construct mimicked the histological appearance of normal oral mucosa. The goal of the project is to investigate the senescence effect of a commonly prescribed N-BP, zoledronic acid (ZOL), on the tissue model’s histoarchitecture and inflammatory cytokine release. When each of the OKF 6/TERT 2 and NHOF monolayer cultures were exposed to zoledronic acid at increasing dosage, viability was reduced proportionally as measured by the MTT assay with NHOF more resistant to zoledronic acid. When exposed to ZOL at 12 µM, OKF 6/TERT 2, not NHOF underwent senescence based on a significant increase in expression of the ß-galactosidase enzyme. Our mucosal model further demonstrated that ZOL induced senescence and potentially impaired reepithelialization of oral mucosa through overactivation of the senescence-associated inflammatory response that leads to SASP (senescence associated secretory phenotype). Analysis of histology further showed degradation of the basement membrane iv accompanied by keratinocyte invasion towards the lamina propria and a significant release of senescence-associated inflammatory cytokines (MMP-3 and IL-8) upon treatment with zoledronic acid. This study therefore suggests that zoledronic acid may impair mucosal re-epithelialization by overactivation of the inflammation response due to senescence.